A triptycene-cored perylenediimide derivative and its application in organic solar cells as a non-fullerene acceptor. (21st August 2017) - Zhang, Li-Peng; Zhao, Wenchao; Liu, Xiaoyu; Jiang, Ke-Jian; Li, Feng-Ting; Hou, Jianhui; Yang, Lian-Ming
Abstract : A triptycene-cored PDI derivative with a 3D molecular structure was designed and synthesized as a promising acceptor in OSCs. Abstract : Perylenediimide (PDI) possesses intense absorption, a low-lying energy level, and a high electron mobility. However, its highly planar conformation and thus strong intermolecular π–π stacking prevents its application as an electron acceptor used in efficient bulk heterojunction (BHJ) organic solar cells (OSCs). Herein, we report a structurally non-planar moleculeTRIP-PDI3, in which a rigid and shape-persistent triptycene (TRIP ) unit is employed as a central unit to collect three PDI arms at the periphery. As an electron acceptor, TRIP-PDI3 exhibits a low-lying LUMO energy level of −3.81 eV similar to that of conventional PCBM, but with an intensive light absorption in the range of 450–600 nm. BHJ OSCs were fabricated usingTRIP-PDI as an electron acceptor and a low band gap polymerPBDT-TS1 as an electron donor, exhibiting a power conversion efficiency (PCE) of 4.53%. The result demonstrates that TRIP is a promising building block for the construction of structurally non-planar PDI derivatives as non-fullerene (NF) electron acceptors for efficient OSCs.